2016
DOI: 10.3109/09537104.2016.1171834
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM2 positively regulates integrin αIIbβ3-mediated platelet functions

Abstract: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) is an Ig-ITIM superfamily member that regulates integrin αIIbβ3 function. We hypothesized that its twin protein, CEACAM2, exerts a similar physiologic role in murine platelets. CEACAM2-deficient mice (Cc2) displayed prolonged tail bleeding times and increased volume of blood loss. Cc2 platelets have moderate integrin αIIbβ3-mediated functional defects with impaired kinetics of platelet spreading on fibrinogen and type I collagen and delayed ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 29 publications
4
20
0
Order By: Relevance
“…Platelet rich plasma (PRP) and washed human or murine platelets were isolated, and platelet aggregation experiments were performed as previously described. [23][24][25]…”
Section: Platelet Preparationmentioning
confidence: 99%
See 3 more Smart Citations
“…Platelet rich plasma (PRP) and washed human or murine platelets were isolated, and platelet aggregation experiments were performed as previously described. [23][24][25]…”
Section: Platelet Preparationmentioning
confidence: 99%
“…Full blood examination parameters were determined as previously described. [23][24][25] Measurement of aand dense-granule exocytosis…”
Section: Hematological Parameter Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…CEACAM1 and CEACAM2 are expressed on a variety of tissues, including platelets (supplemental Figure 1), 66 and get upregulated on the surface of activated platelets, suggesting intracellular pools. 21,22 Findings from KO mouse models showed that both CEACAM1 and CEACAM2 attenuate ITAM receptor-mediated responses, presumably via Shp1 and Shp2, but paradoxically positively regulate integrin-mediated responses, 21,22,83,84 a recurring theme for platelet ITIM-containing receptors. Larger and more stable thrombi after ferric chloride injury in vivo was also demonstrated in CEACAM1-and CEACAM2-deficient mice, indicating that the net functions of CEACAM1 and CEACAM2 is to limit thrombus growth.…”
Section: Other Itim-containing Receptor Contributorsmentioning
confidence: 99%